Character Education Values in The Book of Jāmi'ul Ulūm Wal Hikam and Its Relevance to Commendable Morals in Madrasahs - Ilmiansyach, Ridho; Ulum, Mohammad Samsul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
The hadeeths in the book of Jāmi'ul ulūm wal hikam contain many character values that can be applied to learning commendable morals in the Madrasahs. Studying character values from the hadeeths of the Prophet Muhammad is very important to understand their practical application in learning commendable morals in Madrasahs. This research aims to describe the character values in the hadeeths in the book of jāmi'ul ulūm wal hikam and their relevance to the material of commendable morals in Madrasahs based on KMA No. 183 of 2019. This research aims to identify and describe the character values in the book of Jāmi'ul ulūm wal hikam and its relevance to the material of commendable morals in Madrasahs. This research uses a library research method and qualitative paradigm with a semantic approach to describe the character values in the book of Jāmi'ul ulūm wal hikam. Data collection techniques include reviewing literature, books, notes, and reports on the topics. The analysis technique used in this research is content analysis to describe the character values in the book of Jāmi'ul ulūm wal hikam. Then, the research results are relevant to Madrasahs's moral material. The results show seventeen character values in the book of jāmi'ul ulūm wal hikam. These values are sincerity, wara', affection, restraint of speech, self-control, kindness to animals, humility, shame, istiqāmah, cleanliness, patience, generosity, obedience, zuhud, helpfulness, honesty, and tawakal. The character values of sincerity, obedience, istiqāmah, and patience are relevant to all commendable moral materials in Madrasahss as companion character values in each commendable moral material. Twelve character values apply to the material of commendable morals in the related values: sincerity, affection, restraint of speech, kindness to animals, humility, istiqāmah, cleanliness, patience, obedience, helpfulness, honesty, and tawakal. Keywords: Character Value, The Book of Jāmi’ul Ulūm Wal Hikam, Moral Materials